Risk Perceptions and Acceptance Towards the Uptake of Pertussis Vaccine Amongst the Healthcare Workers in Sabah and Sarawak - Steven, Michal Christina; Jeffery, Stephen (Universiti Putra Malaysia Press, 2021)
Introduction: The incidence of pertussis is increasing amongst adolescents and adults. Therefore, adults require booster vaccination for protection against pertussis infection. Vaccination among healthcare workers (HCW) should be prioritized when a country implements an adult vaccine. However, the coverage of pertussis vaccination is still deficient among HCW due to low-risk perception. Method: This was a cross-sectional study using Survey Monkey (online). A total of 920 HCWs comprising of doctors, assistant medical officers (AMO), nurses, and environmental health officers (EHO) working at the hospitals and district health offices in Sabah and Sarawak were selected to partake in the study using a multistage sampling method. The website containing the questionnaire was given to the participants using either email or WhatsApp. Results: A total of 853 responders of whom 22.2% were doctors, 58.1% were nurses, 10.1% were medical assistants, and 9.6% were environmental health officers responded to the ques-tionnaire. Most of the respondents (81.5%) are willing to receive the pertussis vaccine. The Protection Motivation score was significantly different between those willing and those not willing to take the vaccine (p-value<0.001). Ro-bust path analysis showed that sociodemographic factors (age, the institution of working and prior pertussis vaccina-tion) (p=0.004), threat (p<0.001) and coping pathway (p<0.001) were linked with the willingness to uptake vaccine. Conclusion: The sociodemographic factors of the HCW can affect the willingness of the HCW to uptake the pertussis vaccine directly and indirectly through their risk perception towards pertussis.